Structure-Property Relationships of 3D-Printable Chain-Extended Block Copolymers with Tunable Elasticity and Biodegradability - Kim, Ryung Il; GEONCHANG LEE; Lee, Jung-Hyun; Park, Ji Jong; Lee, Albert S.; Hwang, Seung Sang (AMER CHEMICAL SOC, 2021)
Elastomeric bioscaffolds with tunable elasticity and biodegradability were synthesized via ring opening polymerization of polycaprolactone (PCL) and polylactide (PLA) with a bifunctional polyethylene glycol macroinitiator, followed by chain extension with diisocyanate to form urethane linkages. Through fine tuning of the macroinitiator and PCL/PLA weight fraction and molecular weight, a data set of elastomeric bioscaffolds gives structure-property insights into their thermal, mechanical, and biodegradability properties as they relate to triblock copolymer composition and mechanical weight. These materials were targeted to be 3D-printed by commercial devices, and their unique rheological properties enable impeccable multiscale microstructure formation. Simplicity in synthesis and fabrication as well as tunable biodegradability (1 day to 2 months) and elasticity (modulus 32-94 MPa) suggest the vast wide-ranging utility and prospective application in bioscaffolds for future therapeutic treatments.